2010
DOI: 10.1002/eji.201040539
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐γ and IL‐12 synergize to convert in vivo generated Th17 into Th1/Th17 cells

Abstract: Th1 and Th17 cells are distinct lineages of effector/memory cells, imprinted for reexpression of , by upregulated expression of T-bet and retinoic acid-related orphan receptor ct (RORct) , respectively. Apparently, Th1 and Th17 cells share tasks in the control of inflammatory immune responses. Th cells coexpressing IFN-c and IL-17 have been observed in vivo, but it remained elusive, how these cells had been generated and whether they represent a distinct lineage of Th differentiation. It has been shown that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
126
1
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 47 publications
7
126
1
3
Order By: Relevance
“…Moreover, a subset of human IL-17A-producing CD4 + T cells was found to also produce IFN-γ (Th17/Th1) and both Th17 and Th17/Th1 cells exhibit plasticity toward the Th1 profile when cultured in the presence of IL-12 [4]. Similar findings were also reported in some murine models [5][6][7] suggesting that both human and murine Th17 cells probably represent a transient phenotype [8]. We have also shown that virtually all human memory Th17 cells are contained within the CD161 + fraction of both circulating and tissue-infiltrating CD4 + T cells, and originate from CD161 + precursors present in umbilical cord blood and newborn thymus [9].…”
Section: Introductionsupporting
confidence: 74%
“…Moreover, a subset of human IL-17A-producing CD4 + T cells was found to also produce IFN-γ (Th17/Th1) and both Th17 and Th17/Th1 cells exhibit plasticity toward the Th1 profile when cultured in the presence of IL-12 [4]. Similar findings were also reported in some murine models [5][6][7] suggesting that both human and murine Th17 cells probably represent a transient phenotype [8]. We have also shown that virtually all human memory Th17 cells are contained within the CD161 + fraction of both circulating and tissue-infiltrating CD4 + T cells, and originate from CD161 + precursors present in umbilical cord blood and newborn thymus [9].…”
Section: Introductionsupporting
confidence: 74%
“…Hence, Bending et al 85 have shown that in-vitro-generated Th17 lymphocytes express IL-12Rb2 and are responsive to IL-12, whereas in-vivo-derived Th17 cells lack this IL-12R subunit. 88,92 Subsequent studies have shown that ex vivo Th17 cells can be converted to Th1-like cells in vitro following IFN-c-induced up-regulation of T-bet and acquisition of IL-12Rb2 88,92 (Fig. 2).…”
Section: Th17 Cells a Heterogeneous And Plastic Populationmentioning
confidence: 97%
“…IFN-c). This Th17 phenotype instability was discovered initially using TCR transgenic CD4 + T cells polarized in vitro towards Th17 cells, [83][84][85][86] and more recently with highly purified IL-17A + or IL-17F + populations isolated by cytokine-capture assays 85,87,88 or by cell sorting based on surface expression of reporters (such as Thy-1.1, red fluorescent protein, or enhanced yellow fluorescent protein [eYFP]) that mark cells that have activated the IL-17F 84,89,90 or IL-17A 91 programme. There are some general conclusions regarding Th17 stability that can be drawn from these studies.…”
Section: Th17 Cells a Heterogeneous And Plastic Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a common developmental origin between human Th17 and Th1 cells has been described in various studies [4][5][6]. Accordingly, human Th17 clones appear to express IL-12Rβ2 in addition to IL-23R, and the transcription factor Tbet in addition to RORγt, as well a remarkable proportion of human Th17 cells, produces both IL-17A and IFN-γ, or human Th17 clones can be induced to produce IFN-γ and upregulate T-bet expression when cultured in the presence of IL-12 [7].…”
Section: Introductionmentioning
confidence: 99%